Keefektifan Impact Psychoeducation untuk Meningkatkan Adversity Intelligence Siswa SMK - Asfarina, Lilla Maturizka Ayu (Universitas Sebelas Maret, 2024)
The research aimed to analyze the difference in score increase between the group given psychoeducational using the lead technique and the group given the lead plus impact technique. This research also analyze the interaction between the lead technique and the lead plus impact technique with Adversity Inteligence (AI) level towards increasing students' AI scores. The research method used in this research is a Randomized Factorial Design Experiment for vocational high school students. The research results show a difference in increasing AI scores between groups given lead and lead plus impact interventions with F score=17.2 and P Value=0.00. The group with lead plus impact technique intervention had a higher AI improvement score than the group with lead technique intervention. There was no interaction between the intervention provided and the AI level of the research subjects. From all the research results obtained, the increase in the AI scores of vocational school students was influenced by lead and lead plus impact interventions.